The Pre-Symbiotic Growth of Arbuscular Mycorrhizal Fungi Is Induced by a Branching Factor Partially Purified from Plant Root Exudates - Buee, M.; Rossignol, M.; Jauneau, A.; Ranjeva, R.; Bécard, G. (Molecular plant-microbe interactions, 2000)
Arbuscular mycorrhizal (AM) symbiosis is an association between obligate biotrophic fungi and more than 80% of land plants. During the pre-symbiotic phase, the host plant releases critical metabolites necessary to trigger fungal growth and root colonization. We describe the isolation of a semipurified fraction from exudates of carrot hairy roots, highly active on germinating spores of Gigaspora gigantea, G. rosea, and G. margarita. This fraction, isolated on the basis of its activity on hyphal branching, contains a root factor (one or several molecules) that stimulates, directly or indirectly, G. gigantea nuclear division. We demonstrate the presence of this active factor in root exudates of all mycotrophic plant species tested (eight species) but not in those of nonhost plant species (four species). We negatively tested the hypothesis that it was a flavonoid or a compound synthesized via the flavonoid pathway. We propose that this root factor, yet to be chemically characterized, is a key plant signal for the development of AM fungi.